2009
DOI: 10.1001/archoto.2009.86
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Corticosteroid Injection for Vocal Fold Polyp

Abstract: Percutaneous corticosteroid injection can be used to manage vocal fold polyps with low invasiveness and minimal morbidity. It offers a simple and cost-effective alternative to traditional direct microlaryngoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 11 publications
6
75
0
Order By: Relevance
“…Since then, a number of published studies have demonstrated that VFSI can be applied to treat many structural vocal fold disorders, such as vocal nodules, polyp, cyst, scar, granuloma, and Reinke's edema. [11][12][13] The clinical effectiveness of VFSI was further documented in our recent study that demonstrated significantly higher lesion reduction rates after VFSI than following vocal hygiene education. 22 This study investigated the multidimensional treatment outcomes among the most common vocal fold pathologies.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Since then, a number of published studies have demonstrated that VFSI can be applied to treat many structural vocal fold disorders, such as vocal nodules, polyp, cyst, scar, granuloma, and Reinke's edema. [11][12][13] The clinical effectiveness of VFSI was further documented in our recent study that demonstrated significantly higher lesion reduction rates after VFSI than following vocal hygiene education. 22 This study investigated the multidimensional treatment outcomes among the most common vocal fold pathologies.…”
Section: Discussionmentioning
confidence: 85%
“…39,40 For patients with vocal polyps, this study demonstrated significant improvements in most of the outcome parameters, comparable with results from a previous study. 13 Subsequent analyses revealed that patients with dysphonic symptoms lasting for more than 1 year were more likely to have higher VHI-10 scores postoperatively (Table 3, upper half). It is likely that chronic vocal polyps may present with a higher degree of fibrin deposition, inflammation, and amyloid-like material Atrophic vocal folds recovered completely after 2 months (D).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the vocal fold polyps regress because further collagen production is prevented. [7] Costicosteroids are most effective when used to treat hemorrhagic, fibrous, and fusiform polyps. [8] We found that polyp size was also an important determinant of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In addition, local drug administration is advantageous in patients who cannot tolerate general anesthesia. We delivered the corticosteroid through the cricothyroid membrane.…”
Section: Discussionmentioning
confidence: 99%